CONSUMER PERCEPTION TOWARDS THEIR EXPERIENCES AT TAMAN RIMBA ALAM, PUTRAJAYA - Adizakwan Che Ali; Siti Hawa Baharum; Muhammad Izzudin Mohd Nezam; Shahira A’in Noor Azmi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study investigates consumer perception towards experiences in parks, focusing on design, recreational opportunities, and accessibility. The aim is to understand how these factors influence consumer satisfaction and engagement within park settings. Consumers appreciate well-designed spaces that integrate natural elements, functional amenities, and aesthetic appeal. Recreational opportunities emerged as significant drivers of satisfaction, with consumers valuing a diverse range of activities such as walking trails, playgrounds, and sports facilities. Accessibility was identified as a key factor in ensuring inclusivity and convenience, influencing visitation frequency and duration. The study concludes that a holistic approach to park design, which considers design aesthetics, recreational offerings, and accessibility, is essential for enhancing consumer experiences and promoting park engagement. The objective of this study was to investigate the notable correlation between consumer perceptions of their experiences at Taman Rimba Alam, Putrajaya, focusing on designs, recreational opportunities, and accessibility. This study undertakes a descriptive research design using a quantitative approach as the methodology for the research The demographics and the key variables, which are the designs, recreational opportunities, and accessibility are the main variables in the research framework. Data analysis is based on 98 respondents’ feedback received from the visitors who have visited Taman Rimba Alam, Putrajaya. The data analysis utilized SPSS version 29.0, employing linear regression to test the hypotheses and determine which consumer preferences, such as designs, recreational opportunities, and accessibility, most strongly influence consumer perception of their experiences at Taman Rimba Alam, Putrajaya. The findings revealed that all three hypotheses were supported, suggesting that this study’s results could aid in the development of positive consumer perceptions towards experience enhancement at Taman Rimba Alam, Putrajaya, in an effective and efficient manner.